THE ROLE OF YOUTH ACTIVITIES IN THE DEVELOPMENT OF NON-FORMAL ISLAMIC EDUCATION IN RIMBO BUJANG DISTRICT, TEBO REGENCY, JAMBI PROVINCE - Rasidin Rasidin; Husarida Husarida; Nur Fadlilah Febrilita (Journal of Islamic and Interdisciplinary Research, 2025)
This study investigates the significant contribution of youth in fostering non-formal Islamic education within Rimbo Bujang District, Tebo Regency, Jambi Province. It specifically focuses on the activities of youth organizations such as IPNU, IPPNU, Karang Taruna, and Pemuda Masjid At-Taqwa Muhammadiyah in expanding educational opportunities beyond formal schooling. Using a qualitative approach, the research delves into the key activities undertaken by these organizations. IPNU and IPPNU, as Islamic student associations, play a pivotal role in cultivating the character of young people, promoting moral values and knowledge acquisition through leadership training programs. Karang Taruna empowers youth to develop their potential and serve their communities by initiating productive economic ventures. Meanwhile, At-Taqwa Mosque Youth, being a mosque-centered group, strategically nurtures religious values among the youth through various religious activities, including weekly religious discussions. The findings of this study underscore the substantial and active roles played by youth at different levels in the development of non-formal Islamic education.